Genetic polymorphisms in very important pharmacogenomic variants in the Zhuang ethnic group of Southwestern China: A cohort study in the Zhuang population. Issue 17 (April 2018) - Li, Jing; Guo, Chenghao; Yan, Mengdan; Niu, Fanglin; Chen, Peng; Li, Bin; Jin, Tianbo
Abstract : Abstract: Pharmacogenomics, the study of the role of genetics in drug response, has recently become a focal point of research. Previous studies showed that genes associated with drug detoxification vary among different populations. However, pharmacogenomic information of the Zhuang ethnic group is scarce. The aim of the present study was to screen members of the Zhuang ethnicity in southwestern China for genotype frequencies of very important pharmacogenomic (VIP) variants and to determine the differences between the Zhuang ethnicity and other human populations. We genotyped 80 variants of VIP genes in 100 unrelated healthy Zhuang adults from the Yunnan province of China. Next, we analyzed the genotyping data with Structure and F -statistics ( F st ). We compared our data with those of other populations using the HapMap data set, and observed that the frequency distribution of Zhuang population in Yunnan closely resembles that of JPT. Furthermore, population structure and F st analysis showed that the Zhuang population is closely related to the Shaanxi Han population with respect to genetic background. Our study supplements existing information on Zhuang population pharmacogenomics and provides an extensive overview for developing personalized medicine.